Absorbing and Developing Qualified Fighter Pilots The Role of the Advanced Simulator - Marken, Richard S. (RAND Corporation, 2007)
What qualifications determine whether a fighter pilot is experienced? Surveys of expert pilots revealed that, while flying time is an element of the experience needed for both combat and staff jobs, other things are also important. The Air Force needs to measure and credit different types of experience-including time spent in advanced simulator systems-when revising its definitions of pilot experience.